A methodology for the measurement of the interfacial excess of solute at a grain boundary. (15th July 2016) - Maugis, P.; Hoummada, K.
Abstract: Segregation of solutes on grain boundaries is usually quantified by the peak value of the concentration profile measured across the grain boundary. This procedure is inadequate both from the theoretical and from the practical point of view. Instead, we put forward the concept of interfacial excess of solute, as having a thermodynamic background and being of operative efficiency. Our analyses reveal carbon and boron co-segregation at a martensite lath boundary of a Dual Phase steel. Graphical abstract: Highlights: Quantifying the amount of segregation by the peak concentration is not an adequate procedure. The excess of solute is a proper thermodynamic variable and is of operative efficiency. Co-segregation of boron and carbon at a martensitic lath boundary suggests an atomic-scale layer of cementite.